2009
DOI: 10.5713/ajas.2009.90091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotinamide on Proliferation, Differentiation, and Energy Metabolism in Bovine Preadipocytes

Abstract: This study examined the effects of nicotinamide on proliferation, differentiation, and energy metabolism in a primary culture of bovine adipocytes. After treatment of cells with 100-500 μM nicotinamide, cell growth was measured using 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and cellular lipid content was assessed by Oil Red O staining and a triglyceride (TG) assay. Several factors related to energy metabolism, namely adenosine triphosphatase (ATPase) activity, nitric oxide (NO) conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…In our study, the expression of miR-125b, miR-141, miR-181a, miR-221 and miR-15b were detected in all five tissues ( Table S2 ) and they were associated with feed or N efficiency under different diets ( Table 2 and Table S7 ). Cell proliferation is an important function in lactation initiation, milk precursor absorption and milk component synthesis in mammary gland as well as in rumen and adipose tissues 38 39 . There is evidence that miR-125b, miR-141, miR-181a, miR-221 and miR-205 are involved in cellular proliferation 40 41 42 43 44 , suggesting that these miRNAs play roles in lactation initiation, feed efficiency and N efficiency in dairy cows at different physiological stages by regulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the expression of miR-125b, miR-141, miR-181a, miR-221 and miR-15b were detected in all five tissues ( Table S2 ) and they were associated with feed or N efficiency under different diets ( Table 2 and Table S7 ). Cell proliferation is an important function in lactation initiation, milk precursor absorption and milk component synthesis in mammary gland as well as in rumen and adipose tissues 38 39 . There is evidence that miR-125b, miR-141, miR-181a, miR-221 and miR-205 are involved in cellular proliferation 40 41 42 43 44 , suggesting that these miRNAs play roles in lactation initiation, feed efficiency and N efficiency in dairy cows at different physiological stages by regulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the addition of rumen-protective GABA (RP-GABA) to beef cattle's diet could significantly increase the average daily intake of heat-stressed beef cattle, and improve the nutritional digestibility, growth performance and antioxidant capacity of heat-stressed beef cattle [57]. Nicotinamide is an amide form of nicotinic acid (vitamin B3), which participates in cell proliferation and differentiation [58] and energy metabolism [59] and can improve energy metabolism diseases [60]. Additionally, inducing the use of pyrophosphate (PPI) as an energy enzyme to replace the use of ATP is a potential strategy to deal with the energy crisis [61].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from fat tissues samples using the Trizol reagent (Invitrogen, Carlsbad, CA, USA). For each sample, 1 μg of total RNA was used for first-strand cDNA synthesis as previously described (Liu et al, 2009). Real-Time PCR (qPCR) primers were designed and synthesized (Biosune, Shanghai, China) to assay differentially expressed genes ( Table 2).…”
Section: Rna Extraction and Qpcrmentioning
confidence: 99%